Studi Living Qur’an Dalam Tradisi Nyulur Pupulur Takziah Di Kampung Lembur Jero, Kecamatan Pabuaran, Kabupaten Serang - Aidil Fitri; Sholahuddin Al Ayubi; Zulkifli Reza Fahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the phenomenon of Living Qur’an in the Nyulur Pupulur Takziah tradition in Kampung Lembur Jero, Pabuaran District, Serang Regency. The study aims to describe the implementation of the tradition, identify Qur’anic values, and analyze community perceptions. The method used is descriptive qualitative research through observation, in-depth interviews, and documentation. The results show that this tradition is carried out through a rotating system in providing food for tahlilan activities from the first night until the seventh night. This practice reflects social solidarity and the collective awareness of the community. The Living Qur’an values contained in this tradition include ta‘āwun (mutual assistance), infaq (charitable giving), sincerity, and empathy, which are internalized in daily life. Community perceptions of this tradition tend to be positive because it is viewed as an integration of Islamic teachings and local culture. Thus, Nyulur Pupulur Takziah is a tangible manifestation of the Living Qur’an in the social practices of the community.